Draft Genome Sequence of Bacillus subtilis strain KATMIRA1933 - Karlyshev, Andrey V. (American Society for Microbiology, 2014)
In this report, we present a draft sequence of Bacillus subtilis KATMIRA1933. Previous studies demonstrated probiotic properties of this strain partially attributed to production of an antibacterial compound, subtilosin. Comparative analysis of this strain’s genome with that of a commercial probiotic strain, B. subtilis Natto, is presented.